Peningkatan profesional guru IPS dalam pembelajaran - Yusup Mubaroq; Rahmat; Yayan Sudrajat (Lancar Media Komunikasi, 2023)
Educators are professionals whose job is to plan and implement the learning process, assess learningoutcomes, conduct mentoring and training, and conduct research and community service. This paper aims to find the meaning of the existence of professional social studies educators or teachers. In this case it aims to determine the extent of the important role of a teacher in increasing professionalism in teaching and learning activities, especially social studies teachers. In this study we used a qualitative method. Increasing the Professionalism of Social Sciences teachers has its own challenges to measure the success of student learning activities, so that learning objectives are achieved. Universal social studies lessons are a challenge for every teacher to improve their ability to create interesting teaching methods. Characteristics Skills in the modern era need to be mastered by all social studies teachers from innovation, digitalization and collaboration on the values of life in society. It can be said that the professionalism of social studies teachers greatly influences the values of human civilization on this earth. The qualitative method used in this study is a sociological approach and the application of behavioral psychology theory